2015
DOI: 10.1111/1365-2664.12409
|View full text |Cite
|
Sign up to set email alerts
|

Avian species identity drives predation success in tropical cacao agroforestry

Abstract: Summary1. Avian ecosystem services such as the suppression of pests are considered to be of high ecological and economic importance in a range of ecosystems, especially in tropical agroforestry. However, how bird predation success is related to the diversity and composition of the bird community, as well as local and landscape factors, is poorly understood. 2. We quantified arthropod predation in relation to the identity and diversity of insectivorous birds using experimental exposure of artificial, caterpilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 33 publications
14
100
0
1
Order By: Relevance
“…For example, Puckett and colleagues observed the majority of avian predators species (76%) foraging mainly within 20 m of the woody edge in temperate maize plantations ). Additionally, Maas and colleagues found higher number of predations marks by birds near forest edges in tropical cacao agroforestry, in an experimental study using plasticine caterpillars (Maas et al 2015).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, Puckett and colleagues observed the majority of avian predators species (76%) foraging mainly within 20 m of the woody edge in temperate maize plantations ). Additionally, Maas and colleagues found higher number of predations marks by birds near forest edges in tropical cacao agroforestry, in an experimental study using plasticine caterpillars (Maas et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Insectivorous birds provide significant pest control services , Maas et al 2015, and may complement or replace chemical-based pest control strategies agricultural systems , Maas et al 2015. However, the links between landscape structure and avianmediated insect pest control services are poorly known.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have identified predatory birds controlling pests in coffee and cacao plantations Maas et al 2015), more studies are needed to identify the vertebrate predators that provide pest control services in coffee plantations in Brazil. Also basic biological information regarding the potential negative interactions between vertebrate and arthropod predators in coffee plantations is needed to understand how to maximize this service.…”
Section: Future Perspectivesmentioning
confidence: 99%